2023
DOI: 10.1136/bmjopen-2023-073679
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholders’ perceptions of a nurse-led telehealth case management intervention in primary care for patients with complex care needs: a qualitative descriptive study

Alannah Delahunty-Pike,
Mireille Lambert,
Charlotte Schwarz
et al.

Abstract: ObjectiveWith the onset of the COVID-19 pandemic, telehealth case management (TCM) was introduced in primary care for patients requiring care by distance. While not all healthcare needs can be addressed via telehealth, the use of information and communication technology to support healthcare delivery has the potential to contribute to the management of patients with chronic conditions and associated complex care needs. However, few qualitative studies have documented stakeholders’ perceptions of TCM. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 30 publications
0
11
0
2
Order By: Relevance
“…This imbalance may reflect the priorities of care managers as well as the needs of their clients, both patients and other providers, given the limited time available in a monthly telephonic encounter. They may focus on domains of care that they can do something about, such as connecting patients to supportive services or providing coupons or other assistance to defray medication costs, and/or patients may be unwilling or less willing to disclose challenges until trust is developed [ 23 25 ]. We demonstrate a practical strategy for mining care managers’ notes for barriers to care and unmet social needs, bringing care managers into the process to reflect on the terms that they use to document different findings.…”
Section: Discussionmentioning
confidence: 99%
“…This imbalance may reflect the priorities of care managers as well as the needs of their clients, both patients and other providers, given the limited time available in a monthly telephonic encounter. They may focus on domains of care that they can do something about, such as connecting patients to supportive services or providing coupons or other assistance to defray medication costs, and/or patients may be unwilling or less willing to disclose challenges until trust is developed [ 23 25 ]. We demonstrate a practical strategy for mining care managers’ notes for barriers to care and unmet social needs, bringing care managers into the process to reflect on the terms that they use to document different findings.…”
Section: Discussionmentioning
confidence: 99%
“…Eight studies reported on history taking and patient data collection tasks completed by nurses (Ahmed et al, 2013;Ajay et al, 2016;Anger et al, 2020;Bove, 2010;Cook et al, 2007;Jindal et al, 2022;Kaplan-Dobbs et al, 2021;Rosenman et al, 2006). Nurses conducted a range of diagnostic activities in 45 studies (Ahmed et al, 2013;Ajay et al, 2016;Anger et al, 2020;Anson et al, 2022;Bajis et al, 2020;Barton et al, 2013;Bedelu et al, 2007;Billington et al, 2015;Brennan et al, 2011;Carlisle & Warren, 2013;Chang et al, 2007;Clarke et al, 2018;Cohen et al, 2009;Cook et al, 2007;Delahunty-Pike et al, 2023;Fox & McCorkle, 2018;Frieden et al, 2020;Gilliver et al, 2022;Grimsrud et al, 2014;Howland et al, 2020;Iversen et al, 2020;Jordan et al, 2011;Kompala et al, 2016;Kwak et al, 2021;Macduff et al, 2001;Mallow et al, 2018;McCombe et al, 2022;Momin et al, 2022;Moriyama et al, 2021;Neppelenbroek et al, 2023;Parham et al, 2010;Parham et al, 2023;Parker et al, 2022;…”
Section: Key Tasks Of Nurses Working In Nurse-led Models Of Carementioning
confidence: 99%
“…Nurses conducted a range of diagnostic activities in 45 studies (Ahmed et al, 2013;Ajay et al, 2016;Anger et al, 2020;Anson et al, 2022;Bajis et al, 2020;Barton et al, 2013;Bedelu et al, 2007;Billington et al, 2015;Brennan et al, 2011;Carlisle & Warren, 2013;Chang et al, 2007;Clarke et al, 2018;Cohen et al, 2009;Cook et al, 2007;Delahunty-Pike et al, 2023;Fox & McCorkle, 2018;Frieden et al, 2020;Gilliver et al, 2022;Grimsrud et al, 2014;Howland et al, 2020;Iversen et al, 2020;Jordan et al, 2011;Kompala et al, 2016;Kwak et al, 2021;Macduff et al, 2001;Mallow et al, 2018;McCombe et al, 2022;Momin et al, 2022;Moriyama et al, 2021;Neppelenbroek et al, 2023;Parham et al, 2010;Parham et al, 2023;Parker et al, 2022;Ramakrishnan et al, 2020;Rosenman et al, 2006;Roy et al, 2022;Shaw et al, 2013;Shumbusho et al, 2009;Smits et al, 2020;Some et al, 2016;Stone et al, 2010;Teo et al, 2024;…”
Section: Key Tasks Of Nurses Working In Nurse-led Models Of Careunclassified
See 2 more Smart Citations